Ticagrelor vs. Clopidogrel in Acute Coronary Syndrome Patients With Chronic Kidney Disease After New-Generation Drug-Eluting Stent Implantation - Roh, Ji Woong; Lee, Seung-Jun; Kim, Byeong-Keuk; Hong, Sung-Jin; Kim, Hee-Yeol; Ahn, Chul-Min; Cho, Deok-Kyu; Kim, Jung-Sun; Ko, Young-Guk; Choi, Donghoon; Hong, Myeong-Ki; Jang, Yangsoo (Frontiers in Cardiovascular Medicine, 2022)
Background: The impact of ticagrelor-based dual antiplatelet therapy (DAPT) on acute coronary syndrome (ACS) in patients with chronic kidney disease (CKD) remains unclear. Methods: Data on a total of 1,067 ACS patients with CKD including end-stage renal disease (ESRD) who underwent new-generation drug-eluting stent implantation were extracted from a multicenter registry. This study aimed to compare outcomes of patients treated with ticagrelor- (n=449) and those treated with clopidogrel-based (n=618) DAPT. Outcomes of interest included major adverse cardiac and cerebrovascular events (MACCEs) and bleeding (Bleeding Academic Research Consortium grade 3 or 5) at 12 months. Propensity-score matching (346 pairs) analysis was performed. Results: The patients with ESRD showed the highest MACCE and bleeding rates (P<0.001). There was no difference in the rate of MACCEs between the treatment groups (7.8% vs. 8.4%; hazard ratio [HR]=0.95, 95% confidence interval [CI]=0.56-1.61, P=0.855); however, a trend toward an increased bleeding rate was observed in the ticagrelor-based DAPT group (6.8% vs. 3.8%, HR=1.84, 95% CI=0.93-3.63, P=0.079). Among patients with CKD stage III/IV but without ESRD (277 pairs), the ticagrelor-based DAPT group showed a reduced MACCE rate (3.6% vs. 8.7%, HR=0.41, 95% CI=0.19-0.86, P=0.018) and a similar bleeding rate (5.1% vs. 3.2%, HR=1.61, 95% CI=0.70-3.71, P=0.267), compared with those of the clopidogrel-based DAPT group. Conclusion: The effects of ticagrelor-based DAPT on ischemic and bleeding outcomes of ACS patients with CKD varied according to CKD stage; in ACS patients with CKD without ESRD, ticagrelor-based DAPT reduced MACCE risk without increasing bleeding risks, relative to those observed with clopidogrel-based DAPT.